Pengaruh Postingan Foto Di Instagram @pesonakuningan terhadap Minat Followers Dalam Mengunjungi Wisata Alam Telaga Biru di Kabupaten Kuningan - Fauzi, Egi Nur; Dharta, Firdaus Yuni; Nurkinan, Nurkinan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instagram is one of the internet-based social interaction platforms that is widely used by the public to share information, including information about tourism. The purpose of this study is to find out whether Instagram photo posts @pesonakuningan have a significant influence on the interest of visiting followers to Telaga Biru natural tourism. The independent variable used in this study was Instagram posts (X), while the dependent variable was the interest of visiting followers in visiting Telaga Biru natural attractions. This study adopts the theory of uses and effect as the main theoretical framework, and uses quantitative research methods by using questionnaires as data collection instruments. The analysis used in this study is a simple linear regression analysis. The results showed that photo posts on Instagram @pesonakuningan have a significant effect on the kinat of visiting followers to Telaga Biru natural attractions. Keywords: Social Media, Tourist Attraction, Interested Visit